Pengembangan Media Pembelajaran Menggunakan Kartun Materi Produksi Mata Pelajaran Ips Terpadu Kelas Viii Smp N 1 Sambi Kabupaten Boyolali - RIKA S., HANDRINI (2016)
This research was conducted at SMP N 1 Sambi. The objective of this research was to know the criteria used for the development using the learning media of the 8th grade of production material in the form of cartoon media. In this research, the researcher used the development model developed by Dick and Carey. The development subject of this research was the students of Class VIII B and Class VIII C of SMP N 1 Sambi. The data used for the product development of cartoon media were quantitative and qualitative data. The techniques of data collection used in this research were Questionnair and Interview. The technique of data analysis used the technique of descriptive quantitative analysis in the forms of Validity Test, Reliability Test, Normality Test and Hypothesis Test using Paired Sample T Test. The results of this research showed that the media development of text cartoon in comic cartoon was readable well, the proportion of layout in the comic cartoon had been good, the suitability of background selection in the comic cartoon, the suitability of font type selection and font size selection in the comic cartoon, the precision of pictures used for the material clarity in the comic cartoon, the suitability of pictures with the material, the material presentation had been sequential, the material explanation was vey clear, the visual communication was communicative, simple, attractive, and creative, therefore it could be developed as the learning media in school. The media development of comic cartoon used when the learning occured in the experimental class was effective and could be seen from the result of control class research which showed the results of pre test in which the maximum score was 14, the minimum score was 5, and the average score was 10.09, meanwhile, in the post test, the maximum score was 15, the minimum score was 8 and the average score was 11,75, and in the experimental class, the results of pre test were: the maximum score was 15, the minimum score was 7, and the average score was 11.21, meanwhile, the results of post test showed the highest score was 15 and the lowest score was 11, meanwhile the average score showed 14.45. The results of the two classes showed that the use of learning media in the form of comic cartoon was more efective than the use of lecturing method.